ORGANISATIONAL CULTURE: A CRITICAL FACTOR DETERMINING THE SUCCESSFUL IMPLEMENTATION OF BUSINESS PROCESS REENGINEERING. An Orange Business Services perspective - Garg, Vishal (2010)
Organisations assert to have effectively embarked on business process reengineering (BPR) and indicate remarkable enhancements in their competitive position. Administrative advisors have moderately emphasised the necessity to address the people and organisational concerns, so as to successfully implement BPR. This report illustrates research into business process reengineering and organisational culture change. A literature review is initially used to describe BPR and then, using 7s model of McKinsey, full impact of BPR on an organisation is shown, predominantly in terms of its culture. Further report is focused on the possible ways of managing this crucial dimension, so that the cooperation of organizational culture can be obtained for facilitating the successful BPR implementation. The research conducted in this paper is based on both theoretical and the practical dimensions. The start of this report provides the theoretical dimension by elaborating on the literature whereas the close association with Orange Business Services and the interviews conducted will add the practical and applied dimension to this research work. This amalgamation will help serving the purpose of both the practitioner and the researcher.